Perbedaan Edukasi Menggunakan Media Booklet Dan Audiovisual Terhadap Pengetahuan Ibu Tentang Penanganan Anak Dengan Temper Tantrum - Endang Lestiawati Endang Lestiawati; Nur Aida; Venny Vidayanti (STIKes Payung Negeri Pekanbaru, 2022)
Background: Children with temper tantrums show some reactions that are beyond the control of a child such as screaming, rolling and shouting,this may cause an impact, namely on the child’s intellectual and social development, which becomes less balanced, and that the child often uses tantrums as a pressure to fulfill his desires. Mothers’ lack of knowledge in dealing with children with temper tantrums have a negative impact on the child, therefore, knowledge about handling temper tantrums is needed. Education using booklets and audiovisuals is effective in increasing knowledge, because the media is interesting, not boring and easy to carry everywhere. Objective: To determine the difference between education using booklet and using audiovisual media on mother's knowledge about handling children with temper tantrums. Research Method: This is a quantitative research which uses a quasi-experimental design with pre-test and post-test nonequivalent control group, the research samples are 36 parents selected a purposive sampling technique. The research instrument a questionnaire. Data collected in this research is analyzed using an independent t-test. Results : The mean result before being given health education using booklet media is 13.83 ± 1.465 and after is 17.28 ± 1.320. The mean result of knowledge before being given health education using audiovisual media 13.67 ± 2.114 and after is 17.72 ± 1.708. The paired t-test with booklet media shows a p-value of 0.000 and using audiovisual media shows a p-value of 0.000, while the p-value of the independent t-test test results is 0.524. Conclusion: There is no difference between education using booklet and using audiovisual media on mother'sknowledgeabouthandlingchildrenwithtempertantrums. Keywords: audiovisual, booklet, temper tantrum .